Badminton Specific Agility Test Development Analysis - Eval Edmizal; Vega Soniawan (Performa, 2019)
Researchers modified the specific agility test for badminton using the badminton court and its movements resembled badminton games such as forward, right, left and back steps. This study aims to determine the validity and reliability of specific badminton agility tests. The population in this study were 182 people. The sampling technique uses purposive sampling, so it is determined to be a sample of 100 people. Data collection on badminton specific agility test, shuttle run test, and retesting from badminton specific agility test is done by calculating the time. The validity test in this study correlates the results of the badminton specific agility test with the results of the shuttle run test, while the reliability test by correlating the results of the badminton specific agility test with the results of the retest. Based on data analysis, the level of validity of a Badminton Specific Agility Test is 0.78, which means very good, while the reliability level of a Badminton Specific Agility Test is 0.79, which means it can be accepted.